Access to health services by the parents of individuals with intellectual disability according to their health literacy levels - GÜR, KAMER (My University, 2021)
Objective: Health literacy is designated as a “Social Barrier” to accessing health services. The aim of the study was to determine the access status of the parents of mentally disabled individuals to health services according to their health literacy levels. Methods: The universe of this descriptive study consisted of the parents of individuals with intellectual disability (N:118). The data collection instruments used in the study were the Health Literacy Scale for Turkey-32 and an Access to Health Services Assessment Questionnaire. Ethics Committee permission and approvals were obtained. Results: A statistically significant difference was found between the caregivers’ health literacy levels and their knowledge of how to benefit from health services, their ability to understand the information given to them by health personnel, their ability to correctly communicate their needs, their access to health services and to adequate information, their ability to understand the information gathered and to obtain an appointment from health institutions, their tendency to give up due to the difficulties they faced in procuring an appointment, and their physically being unable to reach health services (p<0.001). Conclusion: The health literacy levels of many of the participants were limited and inadequate. Those with high levels of health literacy were better able to access health information resources, health facilities and services compared to those with low levels of health literacy
Keywords: TIP, ARAŞTIRMA VE DENEYSEL; Klinik Tıp; Klinik Tıp (MED); MEDICINE, RESEARCH & EXPERIMENTAL; CLINICAL MEDICINE; Clinical Medicine (MED); intellectual disability; parent; caregiver; health literacy; access to health services; policy; COMMUNICATION; HIV; MEDICATION; KNOWLEDGE; OUTCOMES; : intellectual disability; parent; caregiver; health literacy; access to health services; policy